2012
DOI: 10.1007/s00392-012-0412-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic protection against ischemia and reperfusion-induced endothelial dysfunction during therapy with different organic nitrates

Abstract: We previously showed that upon repeated administration, the preconditioning-like effects of GTN are attenuated. The present data demonstrate a gradient in the extent of protection afforded by the two nitrates, suggesting that PETN-induced preconditioning is maintained after prolonged administration in a human in vivo model of endothelial dysfunction induced by ischemia. Using isolated human endothelial cells, we propose a mechanistic explanation for this observation based on differential effects of GTN versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
2
12
0
3
Order By: Relevance
“…This finding is consistent with our previous report (10) showing that sildenafil is an effective preconditioning agent in humans. Finally, we confirmed that the preconditioning effect of transdermal GTN in the conduit radial artery is attenuated after repeated exposure for 7 days, consistent with our previous reports (8,20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with our previous report (10) showing that sildenafil is an effective preconditioning agent in humans. Finally, we confirmed that the preconditioning effect of transdermal GTN in the conduit radial artery is attenuated after repeated exposure for 7 days, consistent with our previous reports (8,20).…”
Section: Discussionsupporting
confidence: 93%
“…However, the upregulation of this protective enzyme was attenuated during repeated, daily exposure to GTN, leading to the hypothesis that repeated, daily increases in ROS were responsible for loss of the protective phenotype. The loss of the preconditioning effects of GTN in conduit arteries during repeated daily therapy with GTN is confirmation of this phenomenon in our previous reports (8,20). Since our previous study examined the preconditioning effects of GTN in the resistance vasculature, we felt it important to explore this question in conduit arteries, since this vascular distribution is more relevant to the clinical effects of GTN.…”
Section: Discussionsupporting
confidence: 74%
“…One hypothesis is that the mechanism of this (nonhemodynamic) protective effect depends on the sudden release of ROS during acute GTN administration ( 56 , 304 ): this could trigger opening of the mitochondrial permeability transition pore and a variety of downstream effects, mostly not understood ( 111 , 113 , 129 , 179 ). Therefore, evidence now exists that the transient ROS production associated with GTN administration ( 56 ) has two types of effects: (i) upon short-term GTN administration, it would cause preconditioning-based protection against IR ( 187 ), which, however, can be blocked by antioxidant supplementation (contributing the phenomenon of the antioxidant paradox) ( 79 ); (ii) upon prolonged administration, via oxidative damage, accumulation of ROS would lead to the toxic effects of GTN, such as endothelial and autonomic dysfunction, as described above. PETN also conferred preconditioning effects under chronic conditions ( 187 ), whereas GTN even induced a tolerance to the preconditioning effects, probably based on oxidative damage by GTN-induced RONS formation ( 110 ).…”
Section: Pleiotropic Effects Of Organic Nitratesmentioning
confidence: 99%
“…Interestingly, previous animal studies have reported that theaflavins, a specific type of flavonoids in tea, significantly protect neurons from cerebral IR injury (Cai et al 2006(Cai et al , 2007. In addition, recent human data also demonstrated that improved NO availability (e.g., via nitroglycerin and pentaerythrityl tetranitrate administration) can protect against IR injury (Lisi et al 2012). Based on these previous studies, the cardioprotective effects of regular tea consumption may relate to the protection or attenuation of endothelial IR injury.…”
Section: Introductionmentioning
confidence: 96%